2004
DOI: 10.1016/j.psychres.2003.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Is lateral bias anomalous in early-onset schizophrenia? Selected comparisons with normal populations

Abstract: The aim of this study was to investigate lateral bias in patients with early-onset schizophrenia. Hand, eye, and foot preferences and relative hand skill were examined in early-onset patients (ns44) and matched controls (ns39), and were compared with population estimates. Patients demonstrated a significant excess in mixed handedness (20.5% vs. 8.5%) relative to population estimates and reduced relative hand skill on a pegboard task compared with controls. Left eye preference was significantly less common in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 25 publications
(29 reference statements)
1
14
1
2
Order By: Relevance
“…Our study found no association between age at onset of illness and handedness in schizophrenia/ schizoaffective disorder. This finding is inconsistent with the view that lateralization is anomalous in schizophrenia early in the course of illness, as was demonstrated in the study by Collinson et al 18 .…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…Our study found no association between age at onset of illness and handedness in schizophrenia/ schizoaffective disorder. This finding is inconsistent with the view that lateralization is anomalous in schizophrenia early in the course of illness, as was demonstrated in the study by Collinson et al 18 .…”
Section: Discussioncontrasting
confidence: 84%
“…The degree to which this deviation differs from the onset of schizophrenia amongst the older schizophrenia population is not yet clear, but the evidence suggests that anomalous hand preference may be more common or possibly more severe in patients with early-onset schizophrenia. 18 Although the etiology of handedness, brain asymmetry and schizophrenia is likely to be complex, the discovery of the LRRTM1 gene may reveal new insights in establishment/ maintenance of normal/abnormal brain development, and its relationship with diseases such as schizophrenia. 19 By clinically assessing the possible relationship between handedness, schizophrenia and the LRRTM1 gene, further light may be shed on the importance of the LRRTM1 gene in schizophrenia, which may pave the way for further research.…”
Section: Journal Of Psychiatry • January 2014mentioning
confidence: 99%
“…Subjects were classified as "right," "left," and "either" depending on preference. Foot preference was compared with hand preference to determine hand-foot congruence (Collison et al, 2004;Martin & Machado, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…67) , a esquizofrenia (e.g. 68) , as doenças do sistema imunitá-rio (e.g. 69) ou desordens desenvolvimentais (e.g.…”
Section: Assimetrias Manuais: Período Pré-escolar E Escolarunclassified